The Role of English Department Students in Fostering Maritime Environmental Awareness - HZ Natasya Fitri; Sandi Hana Permata; Prihastini Rossa Indriana; Nabila Salsa Diva (SHS Web of Conferences)
The purpose of this research is to explore the role of English majoring students in fostering awareness of the maritime environment and to increase understanding and actions that support the conservation and preservation of the marine environment. This research is based on a literature review, where the researcher will use secondary data sources to search and find the latest research. The research is conducted in the form of a situation analysis, summary, and author's thoughts about several literature sources that exist and are processed to provide a comprehensive picture of the role and concern of English department students in raising cultural awareness in the sea environment, where in fact we often encounter a lack of awareness around the sea. The literature review in this research was conducted to learn how to conserve mangrove ecosystems. The outline that can be found is that community service activities carried out in Tanjungpinang city, Indonesia, succeeded in increasing public understanding and awareness about the importance of preserving coastal areas, especially mangrove ecosystems.